2016
DOI: 10.1371/journal.pone.0158105
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus Structural Proteins Are the Primary Viral Determinants of Non-Viraemic Transmission between Ticks whereas Non-Structural Proteins Affect Cytotoxicity

Abstract: Over 50 million humans live in areas of potential exposure to tick-borne encephalitis virus (TBEV). The disease exhibits an estimated 16,000 cases recorded annually over 30 European and Asian countries. Conventionally, TBEV transmission to Ixodes spp. ticks occurs whilst feeding on viraemic animals. However, an alternative mechanism of non-viraemic transmission (NVT) between infected and uninfected ticks co-feeding on the same transmission-competent host, has also been demonstrated. Here, using laboratory-bred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…It has recently been demonstrated that the structural genes of Eu-TBEV are prime determinants for TBEV replication and non-viremic transmission among co-feeding I. ricinus , whereas the non-structural genes regulate the cytopathogenicity of TBEV [ 24 ]. The genes encoding the structural proteins of JP-296, JP-554 and Mandal-2009 exhibited the highest numbers of SNPs (data not shown), whereas in another study, the NS2A gene of cDNA-derived TBEV exhibited the highest number of SNPs after cultivation in cell culture and in mice [ 8, 25, 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that the structural genes of Eu-TBEV are prime determinants for TBEV replication and non-viremic transmission among co-feeding I. ricinus , whereas the non-structural genes regulate the cytopathogenicity of TBEV [ 24 ]. The genes encoding the structural proteins of JP-296, JP-554 and Mandal-2009 exhibited the highest numbers of SNPs (data not shown), whereas in another study, the NS2A gene of cDNA-derived TBEV exhibited the highest number of SNPs after cultivation in cell culture and in mice [ 8, 25, 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-systemic transmission can also happen when the host is immune to the infection [46]. Therefore, the force of infection for the questing larvae through non-systemic transmission route is …”
Section: Methodsmentioning
confidence: 99%
“…In summary, both amino acid changes in the E protein of the 40 PS probably contribute to lower virulence in vivo, while the mutation in the NS4B protein most likely arose as a consequence of viral adaptation to PS cells. An underlying role of the structural genes in the pathogenicity for mice was reported previously [75]. Small plaque production by 40 IRE might be the consequence of mutations in the prM protein and 5' UTR, while the mutation in the NS4B protein arose most likely as a consequence of viral adaptation to tick cells.…”
Section: Discussionmentioning
confidence: 63%